Polyelectrolyte-based solid dispersions for enhanced dissolution and pH-Independent controlled release of sildenafil citrate - Woo, Ju Hyeong; Ngo, Hai V.; Nguyen, Hy D.; Gil, Myung Chul; Park, Chulhun; Park, Jun Bom; Cui, Jing Hao; Cao, Qing Ri; Lee, Beom Jin (Heliyon, 2023)
The aim of this study was to design a novel matrix tablet with enhanced dissolution and pH-independent controlled release of sildenafil citrate (SIL), a drug with pH-dependent solubility, by using solid dispersions (SDs) and polyelectrostatic interactions. SIL-loaded SDs were prepared using various polymeric carriers such as poloxamer 188, poloxamer 407, Soluplus®, polyvinylpyrrolidone (PVP) K 12, and PVP K 17 by the solvent evaporation method. Among these polymers, Soluplus® was found to be the most effective in SDs for enhancing the drug dissolution over 6 h in pH 6.8 intestinal fluid. SIL was well dispersed in Soluplus®-based SDs in an amorphous form. When the Soluplus®-based SDs were added in the tablet containing positively charged chitosan and negatively charged Eudragit® L100, the drug release rate was further modulated in a controlled manner. The charge density of the tablet was higher at pH 6.8 than at pH 1.2 due to the polyelectrostatic interaction between chitosan and Eudragit® L100. This interaction could provide a pH-independent controlled release of SIL. Our study demonstrates that a combinatory approach of Soluplus®-based SDs and polyelectrostatic interactions can improve the dissolution and pH-independent release performance of SIL. This approach could be a promising pharmaceutical strategy to design a matrix tablet of poorly water-soluble drugs for the enhanced bioavailability.
Keywords: Controlled release; Differently charged polymers; Enhanced dissolution; Polyelectrostatic interaction; Sildenafil citrate; Soluplus®-based solid dispersion